Apatrobus osuzuyamanus sp. nov., a new patrobine species from Japan, with a comparative study of the male genital morphology of the tribe Patrobini (Coleoptera: Carabidae) - Sasakawa, Kôji; Toki, Wataru (Zootaxa, 2007)
Apatrobus (Apatrobus) osuzuyamanus sp. nov. is described from Kyushu, western Japan (type locality: Mt. Osuzuyama [32°16'N, 131°25'E]). This species is distinguished from A. (A.) ohtsukai Morita by a larger body, a pair of small depressions on the pronotum, and the shape of the aedeagal apex. Based on a comparative study of the male genitalia of several species, the homology of the genital sclerites of the tribe Patrobini are revised and a new terminology is proposed. The implications of present results for Patrobini taxonomy are briefly discussed.